The Relevance of Qur'anic Ethics in Overcoming Hoaxes and Cyberbullying: A Study of Al-Munir's Interpretation and Al-Ghazali's Thoughts - Mahrunnisai Zulfa; laily Liddini (Jurnal El-Thawalib, 2026)
Lies and ridicule in digital media exacerbate the spread of hoaxes and cyberbullying, damaging social relations and morals, the purpose of this study is to examine the relevance of the ethics of the Qur'an in overcoming it through Tafsir al-Munir by Wahbah Az-Zuhaili and the thoughts of Imam Al-Ghazali. This type of research is a literature study, with a thematic interpretation approach, the primary data sources are the Qur'an, Tafsir al-Munir, and Ihya 'Ulumuddin and secondary data sourced from books, journal articles and other documents, data collection techniques through documentation techniques and analyzed using descriptive-analytical analysis techniques and content analysis. The results of the study show that Qur'anic ethics are effective in building digital literacy and moral integrity of society to prevent the spread of hoaxes and acts of cyberbullying in the digital era. The integration of Qur'anic ethical values in the thoughts of Wahbah Az-Zuhaili and Al-Ghazali has proven to be a moral foundation in dealing with various deviations in digital communication.